2022
DOI: 10.1111/nyas.14859
|View full text |Cite
|
Sign up to set email alerts
|

Sexually antagonistic selection on educational attainment and body size in Estonian children

Abstract: Natural selection is a key mechanism of evolution, which results from the differential reproduction of phenotypes. We describe fecundity selection at different parity transitions on 15 anthropometric traits and educational attainment in Estonian children sampled in the middle of 20th century. The direction of selection on educational attainment and bodily traits was sexually antagonistic, and it occurred via different parity transitions in boys and girls. Compared to boys with primary education, obtaining tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Among these, handgrip strength and lung capacity are indices of physical ability and robustness, predicting short-and longterm morbidity and mortality in adult populations (44). In our study population, childhood handgrip strength predicted the reproductive success of men (but not women) (45), while cranial volume predicted educational attainment in both sexes (46).…”
Section: Anthropometric Traitsmentioning
confidence: 89%
See 1 more Smart Citation
“…Among these, handgrip strength and lung capacity are indices of physical ability and robustness, predicting short-and longterm morbidity and mortality in adult populations (44). In our study population, childhood handgrip strength predicted the reproductive success of men (but not women) (45), while cranial volume predicted educational attainment in both sexes (46).…”
Section: Anthropometric Traitsmentioning
confidence: 89%
“…The full dataset for calculation of residuals of morphometric traits consisted of 9,586–15,253 girls (depending on the trait) and 7,170–11,842 boys [age range 6.4–20.0 years, mean = 12.7 ± 6.4 (SD) years, born between 1937 and 1962]. Given the correlations between traits, we also performed principal component (PC) analysis as described in ( 45 ). All linear measures and handgrip strength loaded positively to PC1 (termed hereafter as size) and explained altogether 81% of its variance.…”
Section: Methodsmentioning
confidence: 99%
“…Such selection pressures can be sexually antagonistic and lead to intralocus sexual conflict when there is differential selection on a trait for males and females, but the genetic expression of a trait is determined similarly in each sex. For instance, a study of Estonian schoolchildren born in 1937−1962 found that selection favored stronger, larger, and better‐educated boys and smaller, less‐educated girls 35 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, deaths attributable to external causes such as accidents are lower among parents than among the childless 11 . The pressure of natural (and sexual) selection via childlessness is stronger in men than in women, as shown by Valge et al 35 …”
Section: Introductionmentioning
confidence: 95%
“…Markus Valge, together with his supervisor Professor Peeter Hõrak, has also published several articles [23][24][25][26][27][28]. In these, Juhan Aul data have been juxtaposed with the data of the Estonian Biobank and have been used for checking several essential evolutionary hypotheses of human development.…”
mentioning
confidence: 99%